Tracking the History of Alberta Oil Sands Contaminants Using Lake Sediment Cores - Salat, Alexandre (Université d'Ottawa / University of Ottawa, 2019)
Petroleum hydrocarbons are emitted into the environment via natural and anthropogenic activities. Once emitted, these hydrocarbons can be transported globally, persisting and accumulating in aquatic ecosystems. In the Alberta oil sands region (AOSR), mining activities have significantly altered and polluted the surrounding aquatic and terrestrial environments with heavy metals and various petroleum hydrocarbons including polycyclic aromatic hydrocarbons (PACs). Though PACs have been tracked through time using dated lake sediment cores, separating natural and anthropogenic PACs can be difficult. In the Peace Athabasca Delta (PAD) this task is especially difficult as this region has been receiving annual inputs of naturally eroded bitumen throughout history. Petroleum biomarkers are unique petrogenic compounds (i.e. derived from petroleum) which may provide a secondary proxy to track mining impacts. This thesis investigated the impacts of mining activities on the AOSR and the PAD using two different proxies, PAC and petroleum biomarkers. These two regions were compared to reference lakes to the south and northwest of the Athabasca oil sands formation, in order to provide a natural signal, with minimal oil sands mining contamination. Historically deposited PACs and petroleum biomarkers were analysed in radiometrically dated lake sediment cores from the AOSR and the PAD, Alberta. Sediment profiles in the AOSR (Saline Lake) showed increases in PAC fluxes for both alkylated and parent compounds coeval with mining activities. Alkylated PAC fluxes in reference lakes (Mariana Lake and BM11) increased at the height of oil sands development (1990s). PAD lakes showed no statistical increase in PAC flux through time due to high levels of naturally eroded bitumen entering the system. Parent PAC diagnostic ratios, however, showed clear shifts from pyrogenic (primarily wood burning) in pre-development sediments to petrogenically derived PACs in modern sediments, in both AOSR and PAD lakes, coeval with oil sands development. Petroleum biomarker diagnostic ratios in Saline Lake and PAD lakes remained stable through time, indicating a clear current and historical petroleum signal originating from the AOSR. Reference lakes (Mariana Lake and BM11) showed the greatest change in petroleum biomarkers. Historically, these lakes had signatures uncommon of petroleum sources, however, in recent years petroleum inputs from mining development were revealed by these petroleum biomarkers. This study compared the historical trends of several petroleum hydrocarbons in lake sediment to the historical emissions of these petroleum hydrocarbons from oil sands mining operations. Notably, we show the potential for petroleum biomarkers to trace petroleum hydrocarbon contamination in the environment.
Keywords: Polycyclic aromatic compounds; Petroleum biomarkers; Paleolimnology